Article Review: Synthesis of Bifunctional NiCe/Biochar Catalyst From Palm Shell Waste for Steam Reforming Reaction: Article Review: Synthesis of Bifunctional NiCe/Biochar Catalyst From Palm Shell Waste for Steam Reforming Reaction - Annisya Dwi Putri Zulmi; Tiara Ramadhani; Sella Naomi Br. Sinaga; Diana Zahra Safitri; Syazwana Izni; Khairahma Khairahma; Ahmad Nasir Pulungan (UIN Sulthan Thaha Saifuddin Jambi, 2024)
The use of renewable biomass resources for hydrogen production has gained significant attention due to its environmental benefits and potential to support sustainable energy solutions. This study focuses on synthesizing a bifunctional NiCe/Biochar catalystderived from palm kernel shell waste for steam reforming reactions. The objective is to address challenges such as tar formation during biomass gasification and improve the efficiency and stability of catalysts. The methods involved literature review and analysis of catalyst synthesis, activation, and application. Results showed that incorporating Ce into Ni/Biochar enhanced stability and hydrogen yield, achieving 86.2% carbon conversion and 64.3% maximum hydrogen production under optimal conditions. The conclusions highlight the NiCe/Biochar catalyst's potential for scalable industrial applications in hydrogen production. Future research is recommended to optimize synthesis methods and scale up production to meet increasing energy demands